Hexahelix Concept in The Development of Eco-Tourism Area in The Kelating Traditional Village Eco-Tourism Area, Kerambitan District, Tabanan Regency - I Made Wimas Candranegara; I Wayan Mirta; I Dewa Gede Putra Sedana; Gede Wirata (Iapa Proceedings Conference, 2022)
One of the ecotourism that is developing in Tabanan Regency is ecotourism which is managed by indigenous peoples with the aim of empowering local indigenous communities. One of these actor collaborations is known as the Hexahelix Concept, which is a collaboration of six actors in managing ecotourism areas. This research uses mixed methods with the main focus on qualitative methods and strengthened by quantitative research methods. The indicator used in this research is the role of each actor in solving the problems faced by the manager. There are 13 informants to be interviewed and 75 respondents. The results of this study are the role of government actors as evidenced through the provision of road infrastructure access to the location of the ecotourism area in the Kelating Adat Village, the role of community actors (Indigenous Villages and BUPDA) in the development of ecotourism areas in the Kelating traditional village is realized through the establishment of the Baga Utsaha Padruwen Adat Village (BUPDA). ), the role of private actors in the development of ecotourism areas in the Kelating Traditional Village is realized through its CSR program in the development of ecotourism areas in the Kelating Traditional Village, the role of university actors in the development of ecotourism areas in the Kelating Traditional Village is realized through the implementation of community service activities through the creation of a master plan, and the role of media elements and creative communities in the development of ecotourism areas in the Kelating Indigenous Village by helping to promote and publicize the location of the ecotourism area in the Kelating Traditional Village through social media content created by the creative community, and publication of articles or literature. exclusive putan in newspapers by mass media.